The Conquest Hospital picture archiving and communications system development, 1992 to 1999...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Foord K; Tomlinson N (Journal of Digital Imaging)
Conquest Hospital was a UK regional development site for a pre-Digital Imaging and Communications in Medicine (DICOM) picture archiving and communication system (PACS). The initial system was installed in mid 1992. Identification has been made of data transfer, ergonomic and single point of failure issues in the original PACS, which was called 'iLAN.' This has informed respecification of a DICOM/HTML PACS, the first stages of which have been hospital renetworking and installation of new DICOM 3.0 computed radiography/fluorography and computed tomography/magnetic resonance imaging segments. Final PACS elements are at contract stage. Plans are being completed for linkage of PACS to a clinical information system to create a comprehensive electronic patient record system. Copyright (c) 1999 by W.B. Saunders Company